Mechanical and acoustic properties of macroporous acrylate materials near glass transition. (18th July 2018) - Kovalenko, Artem; Brunet, Thomas; Mondain-Monval, Olivier
Abstract: We study the evolution of the acoustic properties of porous polymer materials in the glass transition temperature domain. First, we study the cross-linked 2-ethylhexyl acrylate (EHA) – 2-ethylhexyl methacrylate (EHMA) non-porous matrices at various compositions and, consequently, various glass transition temperatures. Based on the frequency-temperature equivalence principle, we build master curves in order to determine the bulk ( K 0 ) and shear ( G 0 ) moduli corresponding to ultrasonic frequencies (about 300 kHz). Next, we synthesize some porous samples of these matrices using the emulsion-templated polymerization approach usually known as polyHIPE (for polymerized High Internal Phase Emulsion). We measure the longitudinal sound speed C L for different matrix compositions (at room temperature) or at different temperatures (for the same sample composition). As expected, we show that the sound speed decreases with increasing K 0 /G 0 ratio, i.e. as matrices become softer, which is either due to an increase of EHA content or to an increase of the temperature. This demonstrates how composition and temperature may be used to tune the sound speed in porous polymers. We show that the theoretical predictions using a low-frequency multiple scattering model leads to underestimated values of the sound speed, especially for soft matrix. We attribute this discrepancy to the difference in mechanical properties of the polymer matrix between non porous and porous samples. Graphical abstract: Image 1 Highlights: The mechanical properties of polyacrylate matrices are investigated close to their glass transition temperature. Porous polymer materials from acrylate mixtures are obtained by emulsion templating. Acoustic properties of acrylate porous polymer strongly vary in the glass transition temperature domain. Acoustic transmission strongly decreases as temperature exceeds the glass transition temperatures of these porous materials.